STUDENT AND FACULTY OF ENGAGEMENT IN NONFORMAL EDUCATION - Tri Wijaya; Elihami Elihami; Ibrahim Ibrahim (JURNAL EDUKASI NONFORMAL, 2019)
Actual education applies in association between adults and children. Education in the association between adults and children. Intercourse between adults and adults is not called association education (pedagogical association) because in that association adults accept and take responsibility for their own influence. Pedagogical association exists only between adults and children (people who are not yet mature). However, we must remember that not every association between adults and children is educational. Many relationships and relationships are neutral in nature, which are pedagogical, for example, parents ask to take glasses not because they intend to educate, but because they themselves are reluctant to take. For example, a person who propaganda to sell obscene books to children cannot be called a pedagogical association